Low hand grip strength as an indicator of depression in the Korean population: a large-scale cross-sectional study - Bum Ju Lee (Frontiers Media S.A., 2024)
BackgroundDepression is one of the leading global mental health problems, and hand grip strength (HGS) is associated with depression. However, there have been no studies assessing the association between depression and relative HGS indices combined with waist circumference (WC) and the waist-to-height ratio (WHtR). The objective of this study was to examine the association of depression with absolute and relative HGS indices.MethodsThis was a cross-sectional study based on the Korea National Health and Nutrition Examination Survey from 2014 to 2019. A total of 20,649 participants (8,959 men, 43.4% and 11,690 women, 56.6%) were included. The associations between depression and the HGS indices were analyzed through complex sample binary logistic regression models, which were adjusted for age in Model 1 and various covariates in Model 2.ResultsThe prevalence of depression was 4.58%, with rates of 2.29% for men and 6.34% for women. The prevalence of depression in women was 2.76 times greater than that in men. In men, the mean HGS values in the dominant hand were 35.48 ± 0.75 kg in the depression group and 38.73 ± 0.11 kg in the non-depression group; in women, they were 21.37 ± 0.22 kg in the depression group and 22.77 ± 0.07 kg in the non-depression group. In men, relative HGS indices as HGS/WC, HGS/body mass index, and HGS/WHtR were more strongly associated with depression than were the absolute HGS indices; however, in women, the associations were similar for both absolute and relative HGS indices. The magnitude of the association was greater for men than for women. In both sexes, all the anthropometric indices had a lower association with depression than did the HGS indices.ConclusionLow absolute and relative HGS were negatively associated with depression in the Korean population. But, relative HGS indices were more strongly associated with depression than were absolute HGS and anthropometric indices in men but not in women.